Development of Assessment For Learning (AFL) through the Educandy Application for Middle School Biology Learning - Maryanti, Sri; Hartati, Sri; Trie Kurniawan, Dede; Mukhtar, Siti Nuraeni (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This research-based paper specifically aims to develop, describe and analyze and implement student assessment design products at the secondary school level which are integrated with digital education technology for learning biology with assessment for learning (AFL) format. In this study, the developed AFL design product was resulted in a valid and steady conclusion and became an alternative solution that could be implemented in the post-covid-19 pandemic for high school biology learning. This development research employs the ADDIE model which consists of analysis, design, development, implementation and evaluation stages. The chosen subjects of assessing the AFL design and instruments are lecturers of educational evaluation subject and three expert lecturers consist of one evaluation expert, one media expert, and one biological content expert. Such formulated review and input from expert lecturers serve as a validation of the AFL design instruments and products. In this research-based paper, the researchers describe how the process of making and assessing the feasibility of AFL for high schools biology learning and its implementation when submitted to the Subject Teacher Forum (STF) of Natural Sciences Subject in Subrayon 5 Gunung Halu, Cililin District, West Bandung Regency. Based on the findings of research and development of AFL biology learning in high schools in forms of assessments among the media experts, material experts, teacher evaluation and experts responses, as well as the results of implementation observations in the field, it can be concluded that AFL Biology learning with Educandy application is declared “feasible and effective” to be utilized in the learning process for high schools. The implication of such formulated research is to provide an alternative integrative learning approach for biology learning through the use of AFL Educandy for post-covid-19 pandemic learning.Keywords: assessment for learning, educandy, high schools biology learning